Morphological correlates of corticosteroid-induced changes in prefrontal cortex-dependent behaviors - Cerqueira, João (2005)
Imbalances in the corticosteroid milieu have been implicated in several neuropsychiatric disorders, including depression and schizo-phrenia. Prefrontal cortex (PFC) dysfunction is also a hallmark of these conditions, causing impairments in executive functions such as behavioral flexibility and working memory. Recent studies have suggested that the PFC might be influenced by corticosteroids released during stress. To test this possibility, we assessed spatial working memory and behavioral flexibility in rats submitted to chronic adrenalectomy or treatment with corticosterone (25 mg/kg) or the synthetic glucocorticoid dexamethasone (300 μg/kg); the behavioral analysis was complemented by stereological evaluation of the PFC (prelimbic, infralimbic, and anterior cingulate regions), the adjacent retrosplenial and motor cortices, and the hippocampal formation. Dexamethasone treatment resulted in a pronounced impairment in working memory and behavioral flexibility, effects that correlated with neuronal loss and atrophy of layer II of the infralimbic, prelimbic, and cingulate cortices. Exposure to corticosterone produced milder impairments in behavioral flexibility, but not in working memory, and reduced the volume of layer II of all prefrontal areas. Interestingly, adrenalectomy-induced deleterious effects only became apparent on the reverse learning task and were not associated with structural alterations in the PFC. None of the experimental procedures influenced the morphology of retrosplenial or motor cortices, but stereological measurements confirmed previously observed effects of corticosteroids on hippocampal structure. Our results describe, for the first time, that imbalances in the corticosteroid environment can induce degeneration of specific layers of the PFC; these changes appear to be the morphological correlate of corticosteroid-induced impairment of PFC-dependent behavior(s).